RANCANG BANGUN SISTEM PRESENSI MAHASISWA PENDIDIKAN TEKNIK ELEKTRONIKA MENGGUNAKAN QR CODE DAN FINGERPRINT - Ray Ghina Ramadhanti; Moch. Sukardjo; Diamah, Aodah (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2025)
The current digital and online era has impacted all sectors, including education. However, in educational administration, for example, student attendance in several educational institutions—particularly at Universitas Negeri Jakarta, Electronics Engineering Education Study Program—is still conducted manually. Therefore, an attendance system for Electronics Engineering Education students using QR codes and fingerprints was designed to facilitate the recap of student attendance and eliminate errors in filling out attendance records. The research was conducted using the Research & Development (R&D) method. The design of the attendance system for Electronics Engineering Education students using QR codes and fingerprints employs the ESP32 as the main controller, the AS608 fingerprint sensor as the input, and a 16x2 LCD as the output to display attendance data, which is then forwarded and stored in both a database and the students’ Telegram accounts. The testing results of the AS608 fingerprint sensor in the Pre-Liminary Testing stage showed an error rate of 9.33% with 15 students, while in the Main Field Testing stage, the error rate decreased to 5% with 20 students. The student attendance system for Electronics Engineering Education using QR codes and fingerprints was successfully designed, and the attendance results are sent to each student in real-time.